Language Styles Used in CNN Indonesia Advertorial Articles - Devania Tanjaya; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study aimed to identify the language style based on diction employed by CNN Indonesia in their advertorial articles. The writer analyzed two advertorial articles from the national and lifestyle sections using three indicators from Keraf's language style theory (2006): vocabulary, sentence length, and sentence structure. Additionally, the study was supported by theories of syntax, inversion, and sentences. Conducted using the qualitative method, the study revealed that CNN Indonesia employed all three language styles in their national and lifestyle advertorial articles. The national advertorial article mostly used the formal language style, while the lifestyle advertorial article mostly used the informal and conversational language style. Moreover, the findings showed similarities and differences in the language styles used by both advertorial articles. Some indicators of language style were prominent in one section but not in another. The language style used was influenced by the topic and targeted audience.